Pemberdayaan Perangkat Desa Terampil Bermedia dalam Membangun Kesadaran dan Kepedulian Masyarakat terhadap Lingkungan di Desa Cikeruh Kecamatan Jatinangor Kabupaten Sumedang - Feliza Zubair; Iriana Bakti; Yustikasari Yustikasari (Universitas Prof. Dr. Hazairin, SH, 2019)
The Empowerment of Skilled-Media Village Officials in Building Public Awareness and Concern for the Environment in Cikeruh Village, Jatinangor District, Sumedang Regency The village government staff is the spearhead of the village government duty whose job is to deliver and process various information relating to government programs, both central and regional government. In this digital era, almost all information flow is carried out through social media. For this reason, a skilled and capable village government staff is needed, especially in using and utilizing social media devices. Through social media, the village government able to socialize the government's relay program and other information to residents. The village service of Cikeruh village through media social has not run optimally. Therefore, training in managing social media, especially in the socialization of environmental hygiene issues, must be held. Universitas Padjadjaran is one of the higher education institutions holding the mandate of community service through education and research activities. This community service integrated with student work college was held in Cikeruh village, Jatinangor District, Sumedang Regency. The training method was lecture and discussion methods, as well as hands-on practice. Participants gained various knowledge related to message management and the use of social media, especially Facebook and Instagram. The results of the activity were the increasing of the knowing, attitudes, and behavior of participants in using Instagram and Facebook to increase effort in improving and restructuring the environment in Cikeruh Village.